PRODUKTIVITAS TANAMAN SAWIT (Elaeis guineensis Jacq.) BERUMUR TUA BERDASARKAN KEPADATAN POPULASI DI PTPN XIV UNIT PKS LUWU - Nuradnin Rizkiani; Ratnawati Ratnawati; Sitti Inderiati; Asmawati Asmawati (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2023)
Oil palm is Indonesia's mainstay plantation commodity as a source of income for farmers and plantation companies and a source of foreign exchange. Oil palm is a plant with the highest productivity of vegetable oil with a production age beyond 30 years. To evaluate the productivity of old plants of oil palm, a comparative study was carried out based on the number of different populations per unit area of ​​land. The calculation of oil palm plant production in the form of fresh fruit bunches (FFB) was carried out in old plant population areas with different population numbers per hectare due to population reduction after the productive age of the plants had passed. The calculation results show that the productivity of old oil palm plants (34 and 35 years) is influenced by the number of populations per hectare. Oil palms aged 35 years with higher productivity per unit area were 115 and 118 trees per hectare, but the areas with 100 and 115 populations of oil palms per hectare produced a higher weight of FFB per bunch. For oil palm plantations aged 34 years, populations with higher productivity were 100 and 118 trees per hectare, but a higher average weight of FFB per bunch was found in the areas with 85 and 100 populations per hectare.